Analisis Kalam Khabari dalam Al-Quran Surah Al-Kahfi Ayat 67 Terhadap Ilmu Balaghah - Shofiyatun Nafisah Lubis; Indri Hasnur Kasturi (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This article discusses about the kalam khabari contained in surah al-Kahf verse 67 and also how it relates to the beauty of the Arabic language. Kalam khabari is part of the science of ma'ani in the science of balaghah. The purpose of writing this article is to find out the meaning and purpose of kalam khabari contained in surah al-kahfi verse 67 and its connection with the beauty of the Arabic language. The method used in writing this article is to use a qualitative method using a library research approach or a library method that takes references from previous journals. The results obtained are that what is meant by kalam kahabari is a term in the science of balaghah which refers to words that may be true and may be false, depending on the factual conditions, and the use of the word لن which indicates the emphasis of the negative element of the word, and kalam khabari here is part from the science of ma'ani to the science of balaghah, thus influencing the meaning of words and the beauty of the Arabic language contained in them.